The Site of the House of St Mary of Mountjoy, near Jerusalem - Pringle, Denys (Revue biblique, 2022)
This paper attempts to resolve the question of the precise location of the headquarters of the Spanish military order of Mountjoy, which its leader, Rodrigo Álvarez, former count of Sarria (León), began to build beside the Nāblus road at Mountjoy north of Jerusalem in 1178. Although previous studies have mostly agreed in identifying Mountjoy itself with the ridge known as Ra's al-Mashārif from which pilgrims approaching Jerusalem from the north obtained their first view of the city, suggestions for the location of the order’s house have shifted between Shu'fāt, Tall al-Nasba and Tall al-Fūl. Re-examination of the documentary sources and topographical evidence, however, suggests that the house was established on Ra's al-Mashārif itself, beside an existing chapel belonging to the Patriarch of Jerusalem and referred to in the sources as the tolus patriarche.